Sustainable Fisheries in Digha: Policy and Community-Based Approaches for Marine Conservation - Muthazhagu, M.; Gopinath, Majendiran (International Journal of Accounting and Economics Studies, 2025)
Estuarine ecosystems like the Digha Mohona are highly productive yet vulnerable to economic losses caused by pollution, overfishing, and biodiversity degradation. This study presents a revised Gordon-Schaefer bioeconomic model incorporating an environmental quality index and economic biodiversity metric to evaluate the cost of inaction on ecosystem health. Profit-maximizing dynamics and sensitivity analyses offer insight into optimal fishery yields under various pollution scenarios. To strengthen policy relevance, the study integrates economic tools such as net present value (NPV), maximum economic yield (MEY), and cost-effectiveness of pollution mitigation. Furthermore, the paper explores innovative financial instruments like Blue Bonds, Payments for Ecosystem Services (PES), and marine subsidies to promote sustainable fisheries. Governance frameworks, including co-management models and regulatory incentives, are proposed to align ecological sustainability with economic resilience. While the Digha estuary serves as a regional case, limitations in generalizing findings to global fisheries are acknowledged. By coupling ecological models with policy finance mechanisms, the framework supports both environmental protection and economic valuation of marine resources. The findings advocate for ecosystem-based governance supported by targeted investment, making the case for an integrated, economically viable marine resource management strategy.
Keywords: Coastal Ecosystems; Marine Management; Socio-economic Factor; Fishery; Water